A compact ultrawideband antenna with two band‐notches. Issue 3 (28th January 2013) - Zhai, Huiqing; Ou, Jinxia; Li, Tong; Li, Guihong; Li, Long; Liang, Changhong
Abstract A compact ultrawideband (UWB) antenna with two band‐notched characteristics is presented and investigated in this article.Two conformal U type slots are etched on the patch to generate two notched bands at 3.5 and 5.2–5.8 GHz, which contribute good rejection of interference with WiMAX (3.5 GHz) and wireless local area network (5.2–5.8 GHz), each of which can be controlled independently. The presented antenna can provide an UWB bandwidth with expected notched band, and it has omnidirectional radiation pattern and stable gain at working frequencies according to simulation and measurement results. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:583–586, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27369